KETIDAKTERATURAN LEKSIKAL-GRAMATIKAL SEBAGAI TEKANAN KOGNITIF PADA PANGGILAN DARURAT ANAK: KAJIAN LINGUISTIK FORENSIK - Belvana Cetta Ugama; Nova Rahma Dinna; Amara Shofy Fadhila; Maria Mintowati (INDONESIA: Jurnal Pembelajaran Bahasa dan Sastra Indonesia, 2026)
This study aimed to analyze lexical and grammatical speech irregularities as indicators of cognitive stress in emergency calls made by child witnesses. Using a forensic linguistic approach with the main theory of Speech Disfluency. This study used a qualitative descriptive design. The main data source in this study is a video of an emergency call 119 by a child named Carlos who was in a threatening situation, uploaded to the TikTok application via the account @kmtscript on May 17, 2024. In addition, secondary data were obtained from foreign media reports about Carlos's family (7-Year-Old Hero Calls 911, Saves Family, 2010). Data were collected using the free listening technique with conversational involvement. Data analysis was carried out using the flow model by Miles and Huberman through three main stages: data reduction, data classification, and data interpretation. The results show the dominance of lexical irregularities in the form of filled pauses "um" which imply major delays and difficulty in word retrieval due to heavy cognitive load, as well as lexical revision. Grammatical irregularities manifest as false starts, phrase repetitions, and abandoned utterances resulting from syntactic planning failures. The study concluded that these disfluencies are not simply speech errors but rather valid evidence of psychological trauma and extreme cognitive load when processing memories under threat.